Effect of different straw retention techniques on soil microbial community structure in wheat–maize rotation system - Zhang, Shulin; Li, Meng; Cui, Xinyue; Pan, Yuemin (Frontiers in Microbiology, 2023)
Straw returning in a rotation system is considered an effective measure for improving soil quality and maintaining soil microorganisms. However, there are few reports on the mechanism of crop soil microbial communities under wheat-maize crop rotation and straw returning tillage in China. The aim of this study was to investigate how wheat or maize straw-incorporation practices affect bacterial and fungal communities under wheat-maize rotational farming practices. To clarify the effects of straw incorporation on microbial abundance and composition, soil microbial communities from the different treatments were identified using high-throughput sequencing. Our results showed that before corn planting, wheat and maize straw return reduced the abundance of bacterial microorganisms, and increased their diversity but had no effect on the abundance and diversity of fungi. However, before wheat planting, returning wheat and corn stalks to the field increased the diversity of soil bacteria and fungi, whereas returning corn stalks to the field reduced the diversity of fungi and microorganisms. Straw return significantly increased the relative abundance of Ascomycota in the first season and decreased the relative abundance of Ascomycota in the second season; however, in the second season, wheat straw return increased the relative abundance of Bradyrhizobium, which can promote the soil microbial nitrogen cycle, provide nitrogen to the soil. Wheat and maize straw return increased the relative abundance of Chaetomium, whereas wheat straw return and maize straw return decreased the relative abundance. In addition, we detected two fungal pathogens (Fusarium and Trichoderma) under the two planting patterns, and found that the relative abundance of pathogenic Fusarium increased with wheat straw return (FW and SW). Trichoderma increased after treatment with maize straw return before wheat planting (S group). These results suggest that wheat straw return (FW and SW) and maize straw return might have a negative impact on the pathogenic risk. Therefore, further studies are needed to determine how to manage straw returns in agricultural production.